2020
DOI: 10.1186/s12870-020-02512-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, characterization and expression profiling of gibberellin metabolism genes in jute

Abstract: Background: Gibberellin (GA) is one of the most essential phytohormones that modulate plant growth and development. Jute (Corchorus sp.) is the second most important source of bast fiber. Our result has shown that exogenous GA can positively regulate jute height and related characteristics which mean increasing endogenous GA production will help to get a jute variety with improved characteristics. However, genes involved in jute GA biosynthesis have not been analyzed precisely. Results: Genome-wide analysis id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…A total of 7728 internodes of 124 individuals of P. edulis were measured in the present study. Our results showed that the internode numbers of P. edulis were not significantly increased under exogenous GA treatment compared with the CTRL, consistent with Honi et al [98], who found no significant change in the internode numbers of jute under GA treatment. There are few studies concerning internode numbers, and almost all such studies investigated crops.…”
Section: Effects Of the Exogenous Treatments On The Internode Numberssupporting
confidence: 92%
“…A total of 7728 internodes of 124 individuals of P. edulis were measured in the present study. Our results showed that the internode numbers of P. edulis were not significantly increased under exogenous GA treatment compared with the CTRL, consistent with Honi et al [98], who found no significant change in the internode numbers of jute under GA treatment. There are few studies concerning internode numbers, and almost all such studies investigated crops.…”
Section: Effects Of the Exogenous Treatments On The Internode Numberssupporting
confidence: 92%
“…The role of these phytohormone auxins in developmental regulation is important against the cold condition in plants [ 123 ]. GC motif (enhancer-like element involved in anoxic-specific inducibility) [ 124 , 125 ], GARE motif, P box, and TATC box are a type of gibberellin- (GA-) responsive element that are the important phytohormones responsible for various plant growth and development such as seed germination, shoot elongation, leaf expansion, flower development, and fruit senescence [ 126 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the two chromosome‐level jute genomes, we compared the expression of transcripts and genes that are related to fibre development in the secondary cell wall with phytohormone, especially gibberellin. Gibberellin, the key plant hormone associated with the reduction of plant height by plant breeders during the Green Revolution in the middle of the 20th century, and the main function of which is to promote cell elongation (Honi et al ., 2020). Thus, transcriptome analysis of stem bark grown under either normal conditions or after GA 3 treatment at the vigorous vegetative stage (60 days after germination) in HM179 and KYCG was conducted to identify candidate genes that are involved in fibre development of bast fiber (Table S11).…”
Section: Resultsmentioning
confidence: 99%